The Relationship Between Waist Circumference and Blood Pressure in the Elderly at the Budi Agung Elderly Social Welfare Unit, Kupang City - Alfred Hamonangan Sitorus; Anita Shinta Amat; Deri Tallo Manafe (Cendana Medical Journal, 2025)
Abstract Background : Obesity is a condition where there is an accumulation of excess fat in the body. In obesity, especially central obesity is associated with most diseases such as cardiovascular disease and metabolic syndrome. This results in high morbidity and mortality rates for obese patients. Central obesity is the accumulation of fat in the abdomen as measured by anthropometric measurements of waist circumference (waist circumference). Hypertension is a risk factor for cardiovascular disease, and one of the independent risk factors for hypertension is obesity. The risk of hypertension increases by 1.40 times in people with central obesity. Hypertension is a disease that often occurs in the elderly. Objective: This study aims to determine whether there is a relationship between waist circumference and blood pressure in the elderly at the Budi Agung Nursing Home, Kupang City. Method: This study is a correlation analytic study using a cross-sectional design. The research population is the elderly at the Budi Agung Nursing Home in Kupang City. Sampling is done by using purposive sampling technique and obtained as many as 60 research subjects. Waist circumference was measured using a non- elastic tape measure in a standing position. Blood pressure was measured using a sphygmomanometer Result: Among male respondents, 76.9% had a waist circumference of ≤94.0 cm, 11.5% had a waist circumference of >94.0-102.0 cm, and 11.5% had a waist circumference of >102.0 cm. Female respondents, 23.5% had a waist circumference of ≤80.0 cm, 23.5% had a waist circumference of >80.0-88.0 cm, and 52.9% had a waist circumference of >88.0 cm. on blood pressure, 13.3% normal, 43.3% prehypertension, 31.7% hypertension level 1, 11.7 hypertension level 2. The results of bivariate analysis using the Spearmen test obtained p = 0.019 (r = 0.303). Conclusion: There is a relationship between waist circumference and blood pressure in the elderly at the Budi Agung Nursing Home in Kupang City. Keywords: Waist circumference, blood pressure, elderly